Insect-plant interactions - Voelckel, Claudia; Jander, Georg (Chichester, England : Wiley Blackwell, 2014)
This latest volume in Wiley Blackwell's prestigious Annual Plant Reviews brings together articles that describe the biochemical, genetic, and ecological aspects of plant interactions with insect herbivores. The biochemistry section of this outstanding volume includes reviews highlighting significant findings in the area of plant signalling cascades, recognition of herbivore-associated molecular patterns, sequestration of plant defensive metabolites and perception of plant semiochemicals by insects. Chapters in the genetics section are focused on genetic mapping of herbivore resistance trai.
4 Plant Semiochemicals -- Perception and Behavioural Responses By Insects4.1 Introduction; 4.2 A semiochemicals route to the neuron; 4.2.1 Surfing the surface -- A matter of chemo-physical interaction; 4.2.2 Odorant binding proteins, chemosensory proteins; 4.2.3 Eliciting signals -- Odorant receptors and sensory neuron responses to odorants; 4.2.4 The clean-up company -- Odorant-degrading enzymes; 4.2.5 Odour perception -- Summary; 4.3 Behavioural responses of insects to plant volatiles; 4.3.1 Biotic habitat factors influencing plant odour dispersal and insect orientation.
Edition statement from running title area.
Includes bibliographical references at the end of each chapters and index.
Online resource; title from PDF title page (ebrary, viewed April 14, 2014).
Keywords: Insect-plant relationships; Entomology; Plant cells and tissues; Entomology; Insect-plant relationships; Plant cells and tissues; SCIENCE -- Life Sciences -- Botany; Entomology; Insect-plant relationships; Plant cells and tissues; Electronic books